(untitled) (Italiano LinguaDue, 2025)
Scopo del contributo è proporre una Unità di Formazione (UdF) dedicata al lessico “accademico”. Dopo aver definito l’oggetto, si propone una simulazione, ovvero un ciclo di lezioni attivabile nell’ambito di un corso di italiano L2: essa è pensata per gli studenti internazionali che, durante un periodo di mobilità, si trovano nella duplice condizione di dover sviluppare la lingua della comunicazione e portare avanti un percorso di studi nell’ambito accademico italiano. Attraverso le tecnologie dell’informatica e della comunicazione (TIC) e, nel caso specifico, attraverso lo strumento digitale Wooclap, si propongono attività che coinvolgano attivamente lo studente, permettendo di apprendere e consolidare le parole (nomi, verbi, aggettivi) indicanti relazioni di causa-effetto. Proposed training unit: academic vocabulary and cause-effect relations The aim of this contribution is to propose a Training Unit (TU) dedicated to “academic” vocabulary. After defining the subject matter, a simulation is presented, specifically a series of lessons that can be implemented within an Italian L2 course. This is designed for international students who, during a mobility period, find themselves in the dual situation of needing to develop their communication skills while simultaneously pursuing their studies in the Italian academic context. Utilizing information and communication technologies (ICT), and specifically the digital tool Wooclap, activities are proposed that actively engage students, enabling them to learn and consolidate vocabulary (nouns, verbs, adjectives) that indicates cause-and-effect relationships.